2021
DOI: 10.1002/ppj2.20018
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of temporal UAS‐based imagery analysis to estimate plant maturity date for soybean breeding

Abstract: Estimating the date of maturity of soybean breeding field plots is necessary for breeding line characterization and for informing yield comparisons among varieties. The main drawback of visually dating soybean maturity is the sheer scale of note recording entailed and the frequency at which these notes need to be taken. The overall aim of this study was to build upon prior work in using low-cost UAS-based RGB cameras to estimate soybean maturity date by examining the effect of vegetation index, summary statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
(98 reference statements)
0
18
0
1
Order By: Relevance
“…We compare the performance of our proposed deep learning model against a recent state-of-the-art benchmark created by Volpato et al (2021) where a local regression model is fitted to the RGB color transformation values over time. That is, for each plot and drone flight date, an RGB transformation is performed, and the output is fed into the regression model.…”
Section: Benchmarkmentioning
confidence: 99%
See 4 more Smart Citations
“…We compare the performance of our proposed deep learning model against a recent state-of-the-art benchmark created by Volpato et al (2021) where a local regression model is fitted to the RGB color transformation values over time. That is, for each plot and drone flight date, an RGB transformation is performed, and the output is fed into the regression model.…”
Section: Benchmarkmentioning
confidence: 99%
“…That is, for each plot and drone flight date, an RGB transformation is performed, and the output is fed into the regression model. Volpato et al (2021) demonstrated that using the mean greenness leaf index (GLI) on each plot combined with locally estimated scatter plot smoothing (LOESS) regression results in higher correlations between the predicted and ground truth maturity days.…”
Section: Benchmarkmentioning
confidence: 99%
See 3 more Smart Citations